2014
DOI: 10.1007/s10943-014-9853-z
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Role of Spiritual Counseling in Heart Failure Patients

Abstract: To ascertain the beneficial role of spiritual counseling in patients with chronic heart failure. This is a pilot study evaluating the effects of adjunct spiritual counseling on quality of life (QoL) outcomes in patients with heart failure. Patients were assigned to "religious" or "non-religious" counseling services based strictly on their personal preferences and subsequently administered standardized QoL questionnaires. A member of the chaplaincy or in-house volunteer organization visited the patient either d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Conclusions from the non-randomised trials 32 and observational studies regarding the precise impact of the intervention should be cautious due to risk of selection bias and effect of confounders which were either not reported, or, if they were, adjusted findings were not presented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conclusions from the non-randomised trials 32 and observational studies regarding the precise impact of the intervention should be cautious due to risk of selection bias and effect of confounders which were either not reported, or, if they were, adjusted findings were not presented.…”
Section: Discussionmentioning
confidence: 99%
“…Study design and setting. Eight papers reporting seven evaluation phase randomised controlled trials, [20][21][22][23][24][25][26][27] four feasibility and pilot phase studies/randomised controlled trials, [28][29][30][31] one quasi-experimental study, 32 seven cohort studies, [33][34][35][36][37][38][39] two case-control studies 40,41 and one cross-sectional study 42 were included. The characteristics of included studies are summarised in Table 1 (interventional studies) and Table 2 (observational studies).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Chaplaincy has historically been the recommended intervention and continues to be a common suggestion (Attard, Baldacchino, & Camilleri, 2014;Baldacchino, 2008aBaldacchino, , 2008bBaldacchino, , 2011Bean et al, 2009;Bekelman et al, 2007;Bekelman et al, 2010;Blaber et al, 2015;Blinderman & Billings, 2015;H. Y. L. Chan, Yu, et al, 2016;Cooper & Chang, 2016;Ross & Austin, 2015;Tadwalkar et al, 2014;Williams, Voss, Vahle, & Capp, 2016). Chaplaincy services are the standard of care given in current palliative care guidelines (McCusker et al, 2013).…”
Section: Proposed Interventionsmentioning
confidence: 99%
“…[ 2 ] On the other hand, spiritual interventions have become attractive for many people, and effectiveness of these interventions on various groups of physical-mental patients and healthy individuals has been proved. [ 3 4 5 6 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…For instance, numerous studies have pointed to the role of pastoral counselors and religious experts in providing these services. [ 5 ] Moss and Snodgrass conducted a study on cancer patients and found that health providers should introduce these patients to a pastoral counselor who is expert in religious cases since the minds of these patients are occupied with their religious beliefs. [ 12 13 ] In addition, Memaryan et al .…”
Section: Introductionmentioning
confidence: 99%